2022
DOI: 10.3389/fpubh.2022.1015950
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' knowledge, attitude, and behavior towards antimicrobial resistance and antimicrobial use in food production in China

Abstract: BackgroundAntimicrobial resistance (AMR) can be induced by overuse or misuse of antimicrobials. Few researches were involved in consumers' knowledge and attitude toward antimicrobial use (AMU) in food production. This study was designed to investigate the knowledge and awareness, perception, and attitude of Chinese consumers toward AMU in food production. Their behavior, purchase intention of antimicrobial-free food products, and confidence in information sources were also investigated.MethodsAs a descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In Japan, AMR awareness had not significantly changed despite WHO World Antimicrobial Awareness Week campaigns since 2015 [19]. Surveys conducted in Japan also showed continued misconceptions about antibiotics use [20], which was again echoed by a Chinese survey showing insufficient knowledge and neutral attitudes on AMR among consumers in the food sector [21]. Although culturally dissimilar, the similarities with a recent study on AMR knowledge and awareness among Singaporeans [22] demonstrated the need to improve AMR education.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, AMR awareness had not significantly changed despite WHO World Antimicrobial Awareness Week campaigns since 2015 [19]. Surveys conducted in Japan also showed continued misconceptions about antibiotics use [20], which was again echoed by a Chinese survey showing insufficient knowledge and neutral attitudes on AMR among consumers in the food sector [21]. Although culturally dissimilar, the similarities with a recent study on AMR knowledge and awareness among Singaporeans [22] demonstrated the need to improve AMR education.…”
Section: Discussionmentioning
confidence: 99%
“…Data from other research [38] suggest that while US consumers are generally supportive of such labels, they are less willing to pay for them. Goddard [27] found that 9% of German and 15% of Canadian respondents indicated they would be willing to pay for reduced antibiotic use, while Ding et al [24] found that an astonishing 79.8% of Chinese respondents were willing to pay extra for products free from antibiotics. Whether such stated willingness would be repeated in making purchases remains a question.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of consumers have highlighted their lack of knowledge and widespread misconceptions about the nature of antibiotic resistance and the multitude of potential pathways to resistance [10,11,21,22]. Nevertheless, AMR is widely perceived by consumers to be a potential threat to human health, e.g., in Chile [23], China [24], the USA [25,26], Italy [26], Germany [26,27], the UK [28], Canada [27,29] and the European Union [29]. Swiss consumers were generally not aware of any risks of AMR from food, having a high degree of trust that their food was safe, although expressing some concern about food from other countries [10]; however, this qualitative research was conducted using a very small sample of 14 consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Especially in recent years, due to easier access to media communication, Chinese people have increasing resistance to food additives and are reluctant to buy foods containing large amounts of additives; therefore, it is important to ensure the proper use of food additives and their production. 47 As necessary additives to foods for infants and young children, middle-aged and elderly people, and in certain efficacious foods, the use of nutritional fortification should be regulated. 48,49 Therefore, China has set strict requirements on the addition of vitamins, niacin, folic acid, pantothenic acid, inositol, biotin, choline, amino acids, functional peptides and minerals.…”
Section: General Food Standardsmentioning
confidence: 99%
“…The national standard for food additives GB 2760‐2014 regulates the upper limit of additives such as colorants, flavor enhancers, emulsifiers, anti‐caking agents, coating agents, preservatives and sweeteners in food. Especially in recent years, due to easier access to media communication, Chinese people have increasing resistance to food additives and are reluctant to buy foods containing large amounts of additives; therefore, it is important to ensure the proper use of food additives and their production 47 . As necessary additives to foods for infants and young children, middle‐aged and elderly people, and in certain efficacious foods, the use of nutritional fortification should be regulated 48,49 .…”
Section: China's Food Safety Standards and Regulatory Documentsmentioning
confidence: 99%